1986
DOI: 10.1530/jrf.0.0760425
|View full text |Cite
|
Sign up to set email alerts
|

Proteins secreted by the sheep conceptus suppress induction of uterine prostaglandin F-2  release by oestradiol and oxytocin

Abstract: In Exp. I, 0.5 mg oestradiol or vehicle (0.5 ml absolute ethanol + 0.5 ml 0.9% NaCl) was injected i.v. at 08:00 h on Day 14 (onset of oestrus = Day 0). Blood samples were obtained via a jugular catheter at 30 and 1 min before oestradiol and every 30 min for 10 h afterwards. Plasma was obtained and assayed for 15-keto-13,14-dihydro-PGF-2 alpha (PGFM) by radioimmunoassay. Before oestradiol, PGFM basal values were higher (P less than 0.01) in pregnant (N = 10) than nonpregnant (N = 6) ewes (193 +/- 30 vs 67 +/- 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…(Goff et al, 1993), suggest that factors produced by the horse embryo cause the inhibition of PGF2n release indepen¬ dent from the density of endometrial oxytocin receptors. By contrast, in ovine and bovine species, suppression of oxytocin receptors (Sheldrick and Flint, 1985;Fuchs et al, 1990) coincides temporally with conceptus-induced inhibition of PGF2(1 synthesis Fincher et al, 1986;Spencer and Bazer, 1996). The (Warr and Branda, 1983), and there is evidence that the binding affinity of oxytocin to myometrial membranes is critically dependent on the concentration of cholesterol in the plasma membrane (Fahrenholz et al, 1995 (Fuchs et al, 1990) were observed: these included lower affinity to isotocin and higher affinity to oxytocin antagonists than in bovine endometrium, and complete lack of binding of the VP2-receptor subtype specific agonist.…”
Section: Plasma Oxytocinmentioning
confidence: 82%
“…(Goff et al, 1993), suggest that factors produced by the horse embryo cause the inhibition of PGF2n release indepen¬ dent from the density of endometrial oxytocin receptors. By contrast, in ovine and bovine species, suppression of oxytocin receptors (Sheldrick and Flint, 1985;Fuchs et al, 1990) coincides temporally with conceptus-induced inhibition of PGF2(1 synthesis Fincher et al, 1986;Spencer and Bazer, 1996). The (Warr and Branda, 1983), and there is evidence that the binding affinity of oxytocin to myometrial membranes is critically dependent on the concentration of cholesterol in the plasma membrane (Fahrenholz et al, 1995 (Fuchs et al, 1990) were observed: these included lower affinity to isotocin and higher affinity to oxytocin antagonists than in bovine endometrium, and complete lack of binding of the VP2-receptor subtype specific agonist.…”
Section: Plasma Oxytocinmentioning
confidence: 82%
“…These results confirm previous reports [13,23,24,65] suggesting that expression of endometrial ER, PR, and OTR genes is altered by signals from the conceptus. Doses of exogenous oxytocin or estrogen, which initiate luteolysis in cyclic ewes and cows, fail to cause luteolysis in pregnant ewes or in ewes receiving intrauterine injections of interferon-tau (IFN-T) [19,29,33,35,[66][67][68]. This phenomenon is attributable to very low or absent ER [12,23] and OTR in the endometrium of pregnant ewes [13,37,63,69].…”
Section: Discussionmentioning
confidence: 99%
“…In 1982 a protein was identified that was secreted into the medium when sheep conceptuses were cultured in vitro.|6' The synthesis of this protein appeared limited to the critical day [13][14][15][16][17][18][19][20][21] period when maternal recognition of pregnancy was mediated. The protein was later named oTP-1.…”
Section: Robertsmentioning
confidence: 99%